Răspuns :
p = s- 2; s= p +2
4p + 4s = 48
p/..../
s/..../2/
4p /..../..../..../..../
4s /..../2/..../2..../2/..../2/
48- 2 x 4 = 40
8p = 40
1p = 40 : 8
1p = 5
1p = 5 x 1 = 5
1s = 5+ 2 = 7
4p + 4s = 48
p/..../
s/..../2/
4p /..../..../..../..../
4s /..../2/..../2..../2/..../2/
48- 2 x 4 = 40
8p = 40
1p = 40 : 8
1p = 5
1p = 5 x 1 = 5
1s = 5+ 2 = 7
p=s-2lei
4p+4s=48lei
4(s-2lei)+4s=48lei
4s-8lei+4s=48lei
8s=48lei+8lei
8s=56lei
s=7lei
p=7lei-2lei=5lei
4p+4s=48lei
4(s-2lei)+4s=48lei
4s-8lei+4s=48lei
8s=48lei+8lei
8s=56lei
s=7lei
p=7lei-2lei=5lei